Expression and role of TASK-1 channels in pulmonary vessels and airways - Murtaza, Ghulam; Justus Liebig University Giessen (My University, 2012)
TASK-1 is a member of the two pore domain K+ channel family. Its closing causes a decrease in K+ efflux, depolarization of cell membrane, opening of calcium channels and Ca2+ entry into the cell. This has been reported to occur under hypoxia while volatile anesthetics activate this channel. Consequently, TASK-1 may be involved in mechanisms of hypoxic pulmonary vasoconstriction (HPV) and anesthetics-induced inhibition of mucociliary clearance. In cell culture, the superoxide generating enzyme NOX4 has been considered as a functional partner of TASK-1 in O2 sensing. On this background, we set out to investigate in mice (1) the role of TASK-1 channel in HPV and bronchial constriction, (2) the functional relation between TASK-1 and NOX4 in sensing changes in O2 tension in pulmonary vessels, and (3) the role of TASK-1 in cilia driven particle transport on the tracheal mucosal surface.

TASK-1 ist ein Mitglied der zweiporigen K+-Kanalfamilie. Sein Schluss resultiert in einer Abnahme des Kaliumausstroms, Depolarisierung der Zellmembran, Öffnung von Kalziumkanälen und Ca2+-Einstrom in die Zelle. Es wurde berichtet, dass dies unter Hypoxie geschieht, wohingegen volatile Anästhetika den Kanal aktivieren. Dementsprechend könnte TASK-1 in die Mechanismen der hypoxischen pulmonalen Vasokonstriktion (HPV) und der durch Anästhetika induzierten Hemmung der mukoziliären Clearance involviert sein. Aufgrund von Zellkulturexperimenten wurde angenommen, dass das Superoxid generierende Enzym NOX4 bei der zellulären Sauerstoffmessung als funktioneller Partner von TASK-1 fungiert. Vor diesem Hintergrund sollten in der Maus untersucht werden: 1.) die Rolle von TASK-1 in der HPV und Bronchokonstriktion, 2.) der funktionelle Zusammenhang zwischen TASK-1 und NOX4 im Sauerstoffsensormechanismus pulmonaler Gefäße und 3.) die Rolle von TASK-1 im zilienvermittelten Partikeltransport auf der trachealen Schleimhautoberfläche.
Expression und funktionelle Rolle des TASK-1 Kanals in Lungengefäßen und Atemwegen
Keywords: ddc:610